Identification of Gamma-Amino Butyric Acid Isolates Lactic Acid Bacteria Results from The Isolation of Rusip - Prayitno, S Feta Avila; Suprihadi, Agung; Kusdiyantini, Endang (Biosaintifika: Journal of Biology & Biology Education, 2020)
Gamma-aminobutyric acid (GABA) is a non-protein amino acid produced by glutamate decarboxylation by the enzyme glutamate decarboxylase and it is widely distributed in plants, animals and microorganisms. GABA-producing microorganisms including Lactic Acid Bacteria (LAB) which play a role in the fermentation process of food such as rusip. Rusip is a preserved food of marine fish made from raw anchovy of Bangka-Belitung. The purpose of this study was to obtain LAB isolates through the process of isolation from rusip and identify the presence of GABA. Isolation of LAB was carried out by the pour method on MRS agar and NA medium. The growing colonies were then characterized based on observations of colony morphology, Gram staining, catalase test, motility test, and fermentation type test. LAB isolates obtained were selected to obtain isolates which are capable to produce GABA using the Thin Layer Chromatography (TLC) method. The results of isolation from rusip and inoculation on MRS agar medium obtained, three LAB isolates namely RSP-A1, RSP-A2, and RSP-A3. Their characteristics are Gram positive bacteria, negative catalase test, negative motility test, and belong to homofermentative and heterofermentative bacteria groups. They were also able to produce GABA. Research on GABA from isolates isolated from rusip is a new thing in the world of GABA research. This research provides information that is beneficial to produce GABA easily, cheaply, and efficiently.